The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1128/aem.67.9.4128-4136.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Challenge Temperature and Solute Type on Heat Tolerance of Salmonella Serovars at Low Water Activity

Abstract: Salmonella spp. are reported to have an increased heat tolerance at low water activity (a w ; measured by relative vapor pressure [rvp]), achieved either by drying or by incorporating solutes. Much of the published data, however, cover only a narrow treatment range and have been analyzed by assuming first-order death kinetics. In this study, the death of Salmonella enterica serovar Typhimurium DT104 when exposed to 54 combinations of temperature (55 to 80°C) and a w (rvp 0.65 to 0.90, reduced using glucose-fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(80 citation statements)
references
References 60 publications
(69 reference statements)
4
71
2
3
Order By: Relevance
“…Using laboratory models, it was demonstrated that reducing water activity either by desiccation (24,31) or by addition of solutes (2,12,30,37,38) resulted in increased thermal tolerance. Furthermore, low-water-activity medium (30) and dry environment (24) were found to enhance Salmonella tolerance to sodium hypochlorite and ethanol, respectively.…”
mentioning
confidence: 99%
“…Using laboratory models, it was demonstrated that reducing water activity either by desiccation (24,31) or by addition of solutes (2,12,30,37,38) resulted in increased thermal tolerance. Furthermore, low-water-activity medium (30) and dry environment (24) were found to enhance Salmonella tolerance to sodium hypochlorite and ethanol, respectively.…”
mentioning
confidence: 99%
“…Hernandez et al reported on the stress response of Staphylococcus aureus (17), but there are few reports on the stress response and tolerance of bacteria that cause food poisoning (18). In particular, there are only a few reports of the thermotolerance of enterohemorrhagic E. coli (19).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella is widespread in nature and survives in dry foods for weeks, months, or even years (Chang et al 2013 ;Beuchat and Mann 2010a ;Komitopoulou and Peñaloza 2009 ;Beuchat and Scouten 2002 ;Burnett et al 2000 ;Archer et al 1998 ). Food composition, water activity, and temperature collectively infl uence its survival in foods (He et al 2011 ;Mattick et al 2001 ;Corry 1974 ;Dega et al 1972 ;Moats et al 1971 ). The pathogen exhibits increasing resistance at decreasing water activity during heat treatment (Beuchat and Scouten 2002 ;Doyle and Mazzotta 2000 ;Archer et al 1998 ).…”
Section: Pathogens Of Concern In Low-water Activity Foods and Spicesmentioning
confidence: 95%